INTEGRATING TECHNOLOGY INTO EFL CLASSES FOR YOUNG LEARNERS: CHALLENGES AND THE IMPLEMENTATION OF SAMR MODEL - Endah Aprilia Purwaningrum; Atin Kurniawati (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This qualitative study explores the integration of technology in EFL (English as a Foreign Language) classrooms for young learners, focusing on the challenges and the application of the SAMR (Substitution, Augmentation, Modification, Redefinition) model. Using narrative inquiry through interviews and documentation, the research identifies key challenges, including limited access to digital devices, reliance on parental involvement, difficulties in maintaining student motivation, and challenges in finding curriculum-aligned digital materials. In terms of SAMR implementation, the teacher primarily apply substitution, replacing traditional tools with digital versions like e-textbooks and PDFs, and augmentation, where technology enhances tasks through online quizzes and internet-based material exploration. However, the modification and redefinition stages have not been implemented, largely due to access limitations and the developmental stage of the learners. The findings highlight the need for thoughtful integration of technology that accounts for young learners’ readiness and ensures they are the primary beneficiaries. Integrating digital tools should go beyond trend adoption and focus on creating meaningful, accessible, and motivating learning experiences.